Insurance structure, risk sharing, and investment decisions: An empirical investigation of the implications of individual and group weather index insurance - Munro, Laura (International Food Policy Research Institute, 2017)
Recognition of take-up and transaction cost challenges in individual microinsurance has led to a surge of interest in group microinsurance. Yet few studies have considered the effect of group insurance on the investment decisions of the insured. In the case of weather index insurance, this is an important omission. Analogous to group microcredit, group weather insurance may exacerbate two key challenges depending on the information environment: moral hazard and group pressure. Experimental results from a framed field experiment in Gujarat, India, confirm that group pressure leads to an 8 percent reduction in risk taking in contexts with perfect information and group insurance (relative to individual insurance). The effects of moral hazard are more limited, however. As higher risk taking is associated with higher average agricultural productivity—and thus, development—these findings put a premium on greater attention to group selection, the information environment, and the regulation of payout distribution.